A Geographical investigation of the crimes against property in the «Araç» (Kastamonu/Turkey) district center in terms of crime geography - Atish, E. (L. N. Gumilyov Eurasian National University, 2022)
The different social values and cultural lives of human beings have caused thephenomenon of crime to differ between societies. The concept of crime has always been regardedas an important problem in everyday and social life that has become complicated. It is argued thatin the emergence of crime, it is mostly the psychological and sociological factors that are effective.However, in addition to the various geographical features of the place where the crime occurs, theeffect of the socio-economic characteristics that the people living in the particular place interactwith the environment should not be overlooked either. As a matter of fact, these factors are someof the factors that impact the number and type of crime in any given place.Just as a crime occurs in a geographic location as a result of various variables, variouspreventive factors should come together in an attempt to reduce the number of the crimeand prevent it from being committed in that place. In fact, perceiving crime as a duty of lawenforcement officers and seeking solutions only in this way is a method that is not realistic. Inorder to prevent crime, which is a social event, many disciplines need to work together and theresults of these studies should be evaluated and implemented by the decision makers.In this study, the spatial and temporal distribution of crimes against property, the generalcharacteristics of crimes against property, the numerical and proportional distribution of crimesagainst property and the relationship between the geographic features affecting it and the crimesagainst property were investigated and revealed in the Araç District Center of the Kastamonuprovince within a period of three years (2016-2018). As a result of these data obtained in the study,the reasons for the crimes committed against the property in the Araç District Center, whichwas the area of the investigation were examined and evaluated, and based on the findings, somesuggestions were made in order in an attempt to prevent the crimes and reduce their numbers.
Keywords: 5. Gender equality; 11. Sustainability; 8. Economic growth; 1. No poverty; 16. Peace & justice; 12. Responsible consumption